2020
DOI: 10.1186/s41927-020-00152-5
|View full text |Cite
|
Sign up to set email alerts
|

E-consults: an effective way to decrease clinic wait times in rheumatology

Abstract: Background To evaluate the effect of E-consults on wait times and resource utilization for positive antinuclear antibody (ANA) referrals in outpatient rheumatology. Methods We conducted a pre-post study of E-consult implementation for positive ANA referrals. We retrospectively reviewed “positive ANA” referrals from 1/2015–3/2017. A statistical process control chart was created to display monthly average wait times for in-person clinic visits and to identify special cause variation. Final diagnoses, wait time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Considering the trends observed in this study (an upward trend in symptoms and some colloquial terms/well-known conditions coupled with a downward trend in general musculoskeletal disorder terms and certain specific diagnoses) and still on-going pandemic, rheumatologists should address the increased informational demand for musculoskeletal symptoms and develop effective strategies in delivering clinical care to minimize the potential detrimental impact of the pandemic on outcomes of patients with musculoskeletal disorders. Among these strategies, telerheumatology is gaining specific interest and being rapidly implemented in clinical practice during the pandemic [32][33][34][35][36][37].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Considering the trends observed in this study (an upward trend in symptoms and some colloquial terms/well-known conditions coupled with a downward trend in general musculoskeletal disorder terms and certain specific diagnoses) and still on-going pandemic, rheumatologists should address the increased informational demand for musculoskeletal symptoms and develop effective strategies in delivering clinical care to minimize the potential detrimental impact of the pandemic on outcomes of patients with musculoskeletal disorders. Among these strategies, telerheumatology is gaining specific interest and being rapidly implemented in clinical practice during the pandemic [32][33][34][35][36][37].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…This reduced diagnostic accuracy of telemedicine was also found in prospective cohort studies of new patients from rheumatology clinics in the UK and US 23,24 . Another study showed that telemedicine shortened the wait time for an in‐person visit among patients referred for assessment of positive antinuclear antibody 25 . While noting the relatively low quality of this evidence, it does suggest that while telemedicine may not be as effective as conventional consultation in the diagnosis of new patients, it can provide benefit in terms of earlier access to a rheumatologist.…”
Section: Resultsmentioning
confidence: 63%
“…Back and forth, communication can then occur between the PCP and specialist until either the issue is resolved or there is a decision to have an in-person visit. Over time, possible benefits include increased PCP knowledge, reduced wait times [ 29 ], and reduction in inappropriate in-person visits. Symptom checkers (SCs) are another potential option to accelerate diagnosis, reduce misdiagnoses, and guide patients more effectively through the health care system [ 30 ].…”
Section: Discussionmentioning
confidence: 99%